Screening breast MRI in patients with history of atypia or lobular neoplasia. Issue 3 (10th April 2019) - Chikarmane, Sona A.; Giess, Catherine S.
Abstract: Our goal was to determine outcomes of screening breast MRI in patients with prior history of atypia or lobular neoplasia (LN). Review of the MRI data base revealed 264/7482 (3.5%) screening MRIs in 145 patients with history of atypia or LN. Overall, 39/264 (14.7%) received an abnormal interpretation, with 7.2% BI‐RADS 4 and 5 (19/264) and 7.6% BI‐RADS 3 (20/264). PPV1 was 38.4% (six cancers in 39 BI‐RADS 3, 4, 5); PPV3 was 28.5% (six cancers in 21 biopsies). Screening breast MRI use in this population is low (3.5%), although PPVs are comparable to other high‐risk groups for which breast MRI is recommended.